Correlation between 25-hydroxyvitamin D level of lactating mothers and bone mineral density of infants and analysis of risk factors - Jin Yan; Li Minghui; Ding Wei; Wu Huiwen (Journal of Medical Biochemistry)
Background: Aim was to demonstrate the influencing factors of infant bone mineral density (BMD) and its correlation with serum 25-hydroxyvitamin D (25-(OH)D) in nursing mothers. Methods: 200 children aged 0 č 1 years were rolled into normal group (n=120) and abnormal group (n=80) regarding the results of ultrasound BMD examination. The sunshine duration of infants with different BMD and 25(OH)D, calcium and phosphorus levels of nursing mothers were analyzed, and univariate and multivariate analyses of BMD were implemented. Results: The results revealed that the sunshine duration and serum 25-(OH)D level of nursing mothers in abnormal group were inferior to those in normal group (P<0.05). Additionally, a notable positive correlation existed between sunshine duration, serum 25-(OH)D level of nursing mothers and BMD (r = 0.911 and 0.503, P<0.05). According to Logistic regression analysis, outdoor activity time 0 č 1 h/d, premature infants, and breastfeeding alone were independent risk factors (RFs) for abnormal BMD in infants, and vitamin D(VD) and calcium supplementation were independent protective factors (P<0.05). Conclusions: VD and calcium intake, adequate sunshine duration, mixed feeding, and increasing serum 25-(OH)D can reduce the occurrence of abnormal BMD in infants.